HUBUNGAN STATUS PETANI DAN KEBERLANJUTAN USAHATANI DENGAN EKSISTENSI SUBAK DI KECAMATAN KUTA UTARA KABUPATEN BADUNG - Gentari, Dewi Wulan; Sutjipta, Nyoman; Oka Suardi, I Dewa Putu (JURNAL MANAJEMEN AGRIBISNIS; Vol 6 No 1 (2018): MEI 2018DO - 10.24843/JMA.2018.v06.i01.p03, 2018)
The need of land and water resources tends to increase due to the growth of population number, development importance, and the change of life style.  Competition using land and water in the end will shift their availability for agriculture.  Farmer’s status and farming business continuity will measure subak existence in the middle of land need for non agriculture importance.  This research purpose is to find out the correlation of farmer’s status and farming business continuity with subak existence in North Kuta Sub-district.   Research method uses the descriptive quantitative method.  Respondent numbers are 60 farmer members which are collected in proportional random sampling.  Data analysis technique uses the SEM-PLS analysis.   Research results shows that farmer’s status and farming business continuity has positive influence and it is very significant with the existence of subak.  The indirect influence value which is the influence of farmer’s status through the continuity of farming business is bigger than the direct influence.  This proves that farmer’s status is not yet maximal maintaining the existence of subak.  Variable shaper indicator of farming business continuity has the highest value which means that the variable can be used as a benchmark in maintaining the existence of subak.  Suggestion for Kramasubak in North Kuta Sub-district is that to be expected to be able to be more active in carrying out farming group activities that can help the economy. The implementer in agriculture field/academician can help to change farmer’s mindset and can help in supplying the harvest to local villas or restaurants.  The government can support to prepare rice plant shedding machine completed with the dryer.